Disciplinary Literacies in an Engineering Club: Exploring Productive Communication and the Engineering Design Process. (November 2016) - Shanahan, Lynn E.; McVee, Mary B.; Slivestri, Katarina N.; Haq, Kate
This conceptual article addresses the question: What are the disciplinary literacy practices surrounding the Engineering Design Process (EDP) at the elementary level? Recent attention has focused on developing science, technology, engineering, and math (STEM) skills for U.S. students. In the United States, the Next Generation Science Standards and reforms such as Common Core State Standards have drawn increased attention to relationships between language, literacy, and subject matter content often referred to as disciplinary literacy. In this conceptual article, we argue that literacy educators can make a substantial contribution to the study of engineering education, particularly for underrepresented minorities and girls. We first provide a brief overview of disciplinary literacies. Then, using examples from a research-based after-school club, we explore how disciplinary literacies might contribute to the study of engineering and EDP in elementary settings particularly in relation to: (a) productive communication, (b) vocabulary development, and (c) identity.